2021
DOI: 10.3389/fonc.2021.684021
|View full text |Cite
|
Sign up to set email alerts
|

Role of HOXC10 in Cancer

Abstract: The HOXC10 gene, a member of the HOX genes family, plays crucial roles in mammalian physiological processes, such as limb morphological development, limb regeneration, and lumbar motor neuron differentiation. HOXC10 is also associated with angiogenesis, fat metabolism, and sex regulation. Additional evidence suggests that HOXC10 dysregulation is closely associated with various tumors. HOXC10 is an important transcription factor that can activate several oncogenic pathways by regulating various target molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 110 publications
(227 reference statements)
3
9
0
Order By: Relevance
“…However, the relationship between HOXC10 and the clinical indicators of NPC patients requires further investigation. HOXC10 over-expression enhances tumor proliferation, recrudescence, invasiveness, and drug resistance [5]. Our present study also shows that NPC cell proliferation, invasion, and migration were promoted during high HOXC10 expression but were suppressed by low HOXC10 expression.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…However, the relationship between HOXC10 and the clinical indicators of NPC patients requires further investigation. HOXC10 over-expression enhances tumor proliferation, recrudescence, invasiveness, and drug resistance [5]. Our present study also shows that NPC cell proliferation, invasion, and migration were promoted during high HOXC10 expression but were suppressed by low HOXC10 expression.…”
Section: Discussionsupporting
confidence: 71%
“…In NPC, HOXC6 is associated with poor patient survival [14], and HOXC8 inhibits tumor growth by regulating the glycolytic pathway [15]. Aligning with the oncogenic role of HOXC10 in various tumors [5], our present study found that HOXC10 also promotes NPC cell proliferation and metastasis. We found that HOXC10 expression was elevated in NPC cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These results support the hypothesis that HOXC10 (a HOX gene family transcription factor) is directly regulated by miR-4739. The HOXC10/PI3K/AKT pathway has been evaluated previously [ 46 ]. HOXC10 was identified as an oncogene that promotes malignant phenotypes by activating the PI3K/AKT pathway in esophageal cancer [ 20 ].…”
Section: Discussionmentioning
confidence: 99%